Interobserver Agreement on Clinical Judgment of Work of Breathing in Spontaneously Breathing Children in the Pediatric Intensive Care Unit - de Groot, Marcel G.; de Neef, Marjorie; Otten, Marieke H.; van Woensel, Job B. M.; Bem, Reinout A. (Journal of Pediatric Intensive Care, 2020)
Clinical assessment of the work of breathing (WOB) remains a cornerstone in respiratory support decision-making in the pediatric intensive care unit (PICU). In this study, we determined the interobserver agreement of 30 observers (PICU physicians and nurses) on WOB and multiple signs of effort of breathing in 10 spontaneously breathing children admitted to the PICU. By reliability analysis, the agreement on overall WOB was poor to moderate, and only three separate signs of effort of breathing (breathing rate, stridor, and grunting) showed moderate-to-good interobserver reliability. We conclude that the interobserver agreement on the clinical WOB judgment among PICU physicians and nurses is low.
Keywords: respiratory distress; children; critical care